Analysis of The Influence of Profit Sharing, Ijarah And NPF Financing On The Profitability of Sharia Business Units In Indonesia - Fauzuna Naufal Wijanarko; Rini Dwi Susanti; Darlin Rizki (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
Indonesian statistical data shows significant developments in the Islamic banking sector. This is evidenced by the increase in the number of 20 Islamic Commercial Banks (BUS) with an average asset of 478,831 billion and 13 Islamic Business Units (UUS) with an average asset of 255,943 billion. The purpose of this study was to determine the effect of profit sharing, ijarah funding and NPF on profitability (ROA) in Indonesian Islamic Business (UUS). Profit sharing and ijarah financing is a form of bank business to generate profits in accordance with sharia principles. NPF is bad credit that arises when bank funds are channeled, but can affect bank income. The data source for this research is secondary data in the form of UUS (Maybank Indonesia) financial reports for the 2017-2022 period using a quarterly model. The research method used is a quantitative approach using linear regression analysis techniques. The results of this study indicate that simultaneously profit-sharing financing, ijarah and NPF have a positive effect on ROA. Partial test results, profit sharing and ijarah financing have a significant effect on ROA, while NPF has no significant effect on ROA.